“Determinación De Los Nudos Críticos Operativos Que Alteran La Imagen Institucional Del Hospital "Dr. Teodoro Maldonado Carbo" De La Ciudad De Guayaquil”. - Aspiazu Sarcos, Teófilo Jeovanny (2015)
As a contribution to strengthening the current public health system as a contribution to the field of scientific research, the present study, developed in the Teodoro Maldonado Carbo Hospital of Guayaquil, Guayas province and aims at determining born operating critical points that alter the institutional image. While the Teodoro Maldonado Carbo Hospital is undergoing a process of intervention because they had found several anomalies that were detected when you start this process, in this respect it is feasible and appropriate to investigate the existence of critical points that interrupt normal execution of processes and threads that are derived from the catalog of hospital services, data collection techniques, such as the survey of users and managers interview and direct observation in the same place where the events were used. With the present investigation seeks mutual benefit, meanwhile, found solutions to the problems raised, beneficiaries may be, users, operating personnel and authorities.